2014
DOI: 10.4236/ojped.2014.44035
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Challenges in the Management of Paediatric Intussusceptions in the District Hospital

Abstract: Intussusception is the leading cause of intestinal obstruction in children and its management can be challenging especially in centres with inadequate resources where this problem becomes more daunting. Nineteen cases of intussusception in the paediatric age group which were managed by medical officers in a district Hospital in Ghana are discussed. The outcomes of cases treated by open surgery, and those managed by pneumatic reduction were studied. We highlight the use of an improvised set up used in achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
(14 reference statements)
2
1
1
Order By: Relevance
“…Male preponderance has consistently been reported in the literature. [1,3,8] Eleven patients (50%) were <12 months of age with a peak at 7-8 months, findings are similar to those reported by Tagbo et al [3] who reported 88.3% of cases in infants. Patients with intussusception typically present with a triad of vomiting, abdominal pain, and bloody mucoid stool.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Male preponderance has consistently been reported in the literature. [1,3,8] Eleven patients (50%) were <12 months of age with a peak at 7-8 months, findings are similar to those reported by Tagbo et al [3] who reported 88.3% of cases in infants. Patients with intussusception typically present with a triad of vomiting, abdominal pain, and bloody mucoid stool.…”
Section: Discussionsupporting
confidence: 78%
“…All patients had laparotomy, with ileocolic intussusception being the most common type seen, consistent with previous reports. [4,13] Ten patients (45%) had a manual reduction, while 12 (55%) patients had an intestinal resection, similar to rates reported by Gudugbe et al [1] In a review by Bode, [4] 27.8% of patients who had laparotomy had a bowel resection and anastomosis while Taiwo et al, [12] on the other hand, reported a resection rate of 43.6%; while Tagbo et al [3] reported 31.7%. This is attributable to the delayed presentation and late diagnosis in the hospital, resulting in perforation, and gangrene.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Intussusception is the invagination of a segment of the intestine into the distal segment [ 1 ]. It is a common abdominal emergency in children younger than 5 years presenting with features of intestinal obstruction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%